Association Between Rabbit Café Visitor Experiences and Motivations to Feed Feral Rabbits in Vancouver, British Columbia - Lexis H. Ly; Silvija Grava; Oceania C. Kreutzer; Alexandra Protopopova (Journal of Shelter Medicine and Community Animal Health, 2026)
In Vancouver, British Columbia, feeding feral rabbits is prohibited due to risks to animal welfare and public health, yet feeding remains an ongoing issue in areas where populations of abandoned pet rabbits persist. One potential alternative to feeding animals in the wild is engaging in human–animal interaction opportunities in controlled settings such as rabbit cafés. This short report examined factors associated with visitors’ reported likelihood of feeding feral rabbits after visiting a rabbit café. Non-parametric analyses were used to examine differences in reported feeding likelihood across demographic and experiential variables. Younger visitors reported a higher likelihood of feeding feral rabbits in the future compared with older visitors, while no differences were observed by gender or pet ownership status. Patrons who reported disappointment with their café interactions also reported a higher likelihood of feeding feral rabbits in the future. This study is limited by reliance on self-reported future intentions; further research is needed to understand motivations of individuals who actively feed or are concerned about feral rabbit populations. Understanding how human–animal interaction opportunities shape attitudes and behaviors toward urban free-living animals may help inform visitor education and management strategies that support both public engagement and animal welfare.